-8-8n=-7(7n+7)

Simple and best practice solution for -8-8n=-7(7n+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-8n=-7(7n+7) equation:


Simplifying
-8 + -8n = -7(7n + 7)

Reorder the terms:
-8 + -8n = -7(7 + 7n)
-8 + -8n = (7 * -7 + 7n * -7)
-8 + -8n = (-49 + -49n)

Solving
-8 + -8n = -49 + -49n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '49n' to each side of the equation.
-8 + -8n + 49n = -49 + -49n + 49n

Combine like terms: -8n + 49n = 41n
-8 + 41n = -49 + -49n + 49n

Combine like terms: -49n + 49n = 0
-8 + 41n = -49 + 0
-8 + 41n = -49

Add '8' to each side of the equation.
-8 + 8 + 41n = -49 + 8

Combine like terms: -8 + 8 = 0
0 + 41n = -49 + 8
41n = -49 + 8

Combine like terms: -49 + 8 = -41
41n = -41

Divide each side by '41'.
n = -1

Simplifying
n = -1

See similar equations:

| 3x-2=2x-24 | | y=7-x^3 | | -3m-4m-3(-10m-7)= | | 4(1-5x)-4(-4-6x)=x-4+3x-5 | | -7k-10k-2(3k-4)= | | 6(x-12)=x+7(1+12x) | | 42=-7d | | 6x+10=-22-10 | | 5x+1*5x+1=7 | | 2(3x+2)=6x+4 | | 21+2= | | 5(6+4n)=11(3n+11) | | x^3-4x+8=0 | | 3/2x+8 | | 1/2(x+6)=11 | | 3(x+2)/4=2x+1 | | 9(x+9)=-6(x-1) | | 2/3x-15=28-1/3x | | 4x+8-3x=8x+6-7x | | 15y=14(y+11) | | 9(x-2)/6=3(x+3)/7 | | w-3/7=-3/8 | | -6(-5-4x)=-5(12-3x) | | 2x-3=5+4x | | -6-20=-8-7x-6 | | -a-5=1 | | -7/5+n=0,2 | | 5+(x-5)+(x-4)=10+16(x-10) | | -5c-4-10c= | | -2(9-12b)=-6(9b+3) | | 5(x-2)=8-x | | -7+4n=6n+7 |

Equations solver categories